Validation of a booklet designed to promote comfort of relatives of hospitalized patients - Jaqueline Sena Muniz; Kátia Santana Freitas; Joselice Almeida Góis; Adriana Braitt Lima; Elaine Guedes Fontoura; Marluce Alves Nunes Oliveira (Universidade Federal do Ceará, 2019)
Objective: to validate the content of an educational booklet to promote comfort of relatives of hospitalized patients. Methods: methodological study developed in an Intensive Care Unit carried out in three stages: construction of the educational booklet, expert validation, and semantic analysis. The Content Validity Index was used to analyze the degree of relevance and pertinence of the content and the images; values ≥0.80 were adopted. Results: the booklet obtained a satisfactory evaluation in to the evaluated criteria, with an overall Content Validity Index of 0.87. Items that did not reach the content validity index adopted were reformulated. The evaluation made by the judges evidenced that the content was adequate to the main information needs. Conclusion: the content of the educational booklet presented adequate validity indices, thus representing an aid to clarify doubts of relatives, and being, therefore, a tool for health education.